2016
DOI: 10.1136/jmedgenet-2016-104058
|View full text |Cite
|
Sign up to set email alerts
|

Survival and causes of death in patients with von Hippel-Lindau disease

Abstract: vHL survival has improved over time and has become closer to that of siblings without vHL and the general population. Even though the risk of vHL-related death has decreased significantly, the main cause of death is still CNS hemangioblastomas and hence improved treatment options are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 30 publications
(52 reference statements)
4
72
1
3
Order By: Relevance
“…Recently, in line with our results, a national study in Denmark (n=143) showed that the life expectancy improved to 67 years for men and 60 years for women. And they demonstrated that VHL survival was highly dependent on a person’s birth year; the younger the patient is, the longer is the survival 21. In contrast, our study showed that birth year was not an independent risk factor for overall survival (HR 0.99, 95% CI 0.97 to 1.02, P=0.565).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Recently, in line with our results, a national study in Denmark (n=143) showed that the life expectancy improved to 67 years for men and 60 years for women. And they demonstrated that VHL survival was highly dependent on a person’s birth year; the younger the patient is, the longer is the survival 21. In contrast, our study showed that birth year was not an independent risk factor for overall survival (HR 0.99, 95% CI 0.97 to 1.02, P=0.565).…”
Section: Discussioncontrasting
confidence: 73%
“…However, Binderup and his team found that female patients had a mortality hazard that were twice as high as male patients, and the effect was more evident for missense mutation carriers (HR 4.75, P=0.004). They attributed the result to hormonal effects on tumorigenesis, but the mechanisms were not clear 21. The inconsistency between the two cohorts is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifelong surveillance is, therefore, mandated given ongoing risks for tumor development and malignant growth with increasing age, and evidence that longitudinal surveillance in vHL limits morbidity and mortality (14)(15)(16). Multiple groups have developed surveillance guidelines (Table 3).…”
Section: Cancer Screening/surveillance Protocolsmentioning
confidence: 99%
“…Historically, substantial mortality was attributable to RCC, pancreatic NET, and CNS hemangioblastoma (11). Fortunately, these risks have been mitigated in recent years by the institution of comprehensive surveillance paradigms, leading to early recognition of tumors and their multidisciplinary management (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%